Translation, cross-cultural adaptation, and reliability of the Workplace Sitting Breaks Questionnaire into Brazilian Portuguese - Silva,Alexandre Reinaldo (2021)
SUMMARY OBJECTIVE: This study aimed to translate, adapt, and analyze the reliability of the Workplace Sitting Breaks Questionnaire (SITBRQ) for use in Brazil. METHODS: This is a cross-sectional study. The translation and cross-cultural adaptation were conducted considering the following six phases: translation, synthesis of translations, back translation, analysis by a committee of experts, test of the pre-final version, and final version. We included workers aged 18 years or above, both genders, and able to understand, read, and write in Brazilian Portuguese. The final version was applied to workers in two moments (i.e., test and retest), with an interval of 7 days, for reliability calculation. RESULTS: In the translation and cross-cultural adaptation phase, the pre-final version was applied to a sample of 35 workers. For item a of the SITBRQ, there was 100% understanding by respondents, while item b was understood by 94.28%. The reliability phase was conducted with 115 workers. For both items, almost perfect was identified with kappa >0.81. CONCLUSIONS: The SITBRQ version into Brazilian Portuguese has adequate adaptation and excellent values of reliability.